2021
DOI: 10.1080/10807039.2020.1870865
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and geographic patterns of cetacean-based food product consumption and potential mercury exposure within a Caribbean whaling community

Abstract: Background: Exposure to mercury (Hg) through the consumption of seafood is a major public health concern. The tissues of high trophic level marine organisms, such as cetaceans, often contain high concentrations of Hg compared to lower trophic level species. The archipelagic Caribbean nation of St. Vincent & the Grenadines supports two related whaling operations, which produce food from cetaceans for human consumption. A recent study reported that Hg concentrations in tissue samples from one of these whaling op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…When researchers were absent from the field site, communication with whalers and other local experts was maintained via email and online messaging. Field methods also included dietary surveys among potential whale-based food product consumers in the general public (n = 921, see Fielding et al, 2021); archival research; and tissue sample collection for ecotoxicological analysis (see McCormack et al, 2020). Whaling methods were investigated through interview surveys with whalers, archival research, and field observations.…”
Section: Data Collection (2007-2017)mentioning
confidence: 99%
See 3 more Smart Citations
“…When researchers were absent from the field site, communication with whalers and other local experts was maintained via email and online messaging. Field methods also included dietary surveys among potential whale-based food product consumers in the general public (n = 921, see Fielding et al, 2021); archival research; and tissue sample collection for ecotoxicological analysis (see McCormack et al, 2020). Whaling methods were investigated through interview surveys with whalers, archival research, and field observations.…”
Section: Data Collection (2007-2017)mentioning
confidence: 99%
“…The health implications of mercury intake are significant, but poorly understood. Additional recent studies have shown that the vast majority (77.4%) of the SVG population consumes cetaceanbased food products, often in excess of safe weekly limits (Fielding et al, 2021). Investigating the health effects of cetacean products is critical from a public health perspective.…”
Section: Emerging Issues and Recommendations For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Harpooned whales are hauled alongside or into the boat and brought to shore to be processed into food for human consumption. The first line of research to be discussed here considers the patterns of consumption of, and demand for, odontocete-based food products within the SVG public; these patterns of consumption and demand drive current levels of exploitation [11]. It is noted, though, that the impact of this exploitation on regional odontocete populations is difficult to determine in the absence of baseline data on the size and structure of the odontocete populations [9].…”
Section: Introductionmentioning
confidence: 99%